Pathophysiological characteristics of preproinsulin‐specific CD8+ T cells in subjects with juvenile‐onset and adult‐onset type 1 diabetes: A 1‐year follow‐up study. Issue 1 (10th May 2017) - Paul, Mahinder; Badal, Darshan; Jacob, Neenu; Dayal, Devi; Kumar, Rakesh; Bhansali, Anil; Bhadada, Sanjay Kumar; Sachdeva, Naresh
Abstract : Aims/Hypothesis: Among the beta‐cell associated antigens, preproinsulin (PPI) has been shown to play a key role in the pathogenesis of type 1 diabetes (T1D). PPI‐specific autoreactive CD8+ T cells emerge early during beta‐cell destruction and persist in peripheral circulation during diabetes progression. However, the influence of insulin therapy on phenotype of autoreactive CD8+ T cells in T1D including, juvenile‐onset T1D (JOT1D), and adult‐onset T1D (AOT1D) is not yet known. Methods: We followed the time course of PPI‐specific CD8+ T cells in JOT1D and AOT1D subjects that achieved glycemic control after 1 year of insulin therapy, using major histocompatibility complex‐I (MHC‐I) dextramers by flow cytometry. Results and Discussion: At follow‐up, PPI‐specific CD8+ T cells could be detected consistently in peripheral blood of all T1D subjects. Proportion of PPI‐specific effector memory (TEM ) subsets decreased, while central memory T (TCM ) cells remained unchanged in both groups. Expression of granzyme‐B and perforin in PPI‐specific CD8+ T cells also remained unchanged. Further, on analysis of B‐chain and signal peptide (SP) specific CD8+ T cell responses separately, we again observed decrease in TEM subset in both the groups, while increase in naive (TN ) subset was observed in B‐chain specific CD8+ T cells only. Conclusion: Our study shows that PPI‐specific CD8+ T cells can be detected in both JOT1D and AOT1D subjects over a period of time with reliable consistency in frequency but variable pathophysiological characteristics. Insulin therapy seems to reduce the PPI‐specific TEM subsets; however, the PPI‐specific TCM cells continue to persist as attractive targets for immunotherapy.